2012 nurse's drug handbook. (Burlington, MA : Jone and Bartlett Learning, 2012)
"New drug entries include: anti-inhibitor, coagulant complex, ceftaroline, dabigatran, deferoxamine, denosumab, everolimus, ferumoxytol, fingolimod, ibandronate, lurasidone, dydrochloride, pegloticase, tesamorelin."--Back cover
Overview of pharmacology -- Principles of drug administration -- Drug therapy and the nursing process -- Individual drugs (organized alphabetically).
Includes index.
Keywords: DRUG THERAPHY